Protecting livelihoods from drought and flooding in Mozambique: building resilience through nutritious sweetpotato. Project profile - International Potato Center (International Potato Center, 2019)
Mozambique suffers from floods and droughts that can decimate crops but sweetpotato offers reliable yields under a range of adverse environmental conditions. This project builds on CIP’s work to increase production and consumption of sweetpotato in selected areas. It focuses on distributing disease-free planting material, training seed producers and smallholders in growing, harvesting and marketing the crop, as well as working to raise awareness of ways to introduce sweetpotato into people’s diets, particularly targeting households with children under five years old.